VESHENKA QO’ZIQORININI YETISHTIRISHNING BIOKIMYOVIY INOVATSION TEXNOLOGIYALARNI ISHLAB CHIQISH. - Xudanov , Ulug’bek; Sharifov , G’ulom; Xolboyev , Orif (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
Abstract: The article studied the artificial cultivation of oyster mushrooms in tannid-tanned blocks, and can be used in the cultivation of edible higher basidiomycetes, in particular oyster mushrooms. The method of growing mushrooms includes the preparation and heat treatment of lignocellulosic waste from agriculture and forestry, the introduction of mycelium and the formation of tannide-tanned mushroom blocks.